Retinal and Choroidal Vascular Perfusion and Thickness Measurement in Diabetic Retinopathy Patients by the Swept-Source Optical Coherence Tomography Angiography - Liu, Tingting; Lin, Wei; Shi, Genggeng; Wang, Wenqi; Feng, Meng; Xie, Xiao; Liu, Tong; Zhou, Qingjun (Frontiers in Medicine, 2022)
Abstract Purpose: To observe the changes in retinal and choroidal microstructures in patients with different stages of diabetic retinopathy (DR) and to evaluate the vascular perfusion of retina and choroid retinal thickness, retinal and choroidal vessel density by the swept-source optical coherence tomography angiography (SS-OCTA). Methods: Subjects were divided into three groups: healthy control group (30 cases, 51 eyes), non-proliferative diabetic retinopathy (NPDR, 42 cases, 71 eyes) and proliferative diabetic retinopathy (PDR, 31 cases, 53 eyes). The area of the foveal avascular zone (FAZ), retinal and choroidal vascular perfusion, and the deep vascular complexes, including the intermediate capillary plexus (ICP) and deep capillary plexus (DCP) within the radius of 3mm, 6mm, 9mm, and 12mm around the fovea were measured by SS-OCTA. Results: Compared with the healthy control group, DR patients presented significantly increased fovea avascular area, while vessel density (VD) in the ICP and DCP, vascular perfusion rate, and the retinal thickness were considerably decreased. There were significant differences in the retinal thickness, ICP, and DCP vessel densities between the control and NPDR groups, or control and PDR groups, or PDR and NPDR groups. The deep vascular perfusion rate also significantly differed between the control and PDR groups, but there was no significant difference between the PDR and NPDR groups. The choroidal perfusion exhibited significant differences across different areas and amongst the three groups. Furthermore, the choroidal thickness showed a significant difference between the PDR and NPDR groups. Conclusion: Our results showed significant differences in the area of the avascular fovea and the VD of deep vascular complexes between DR patients and healthy control subjects. Moreover, there were significant differences in retinal VD, especially in the deep-retinal regions, choroidal perfusion, and the volume of large vessel choroid in DR patients with different degrees of disease severity. Notably, SS-OCTA provided in-depth information for detecting the potential VD damage in DR patients caused by a multitude of factors. Keywords: Diabetic retinopathy; Swept-source optical coherence tomography angiography; deep capillaries; choroidal vascular perfusion; retinal vascular perfusion.